The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00402-016-2441-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical tests and magnetic resonance imaging have limited diagnostic value for triangular fibrocartilaginous complex lesions

Abstract: According to this study, clinical tests and MR imaging findings are of very limited diagnostic value for the diagnosis of TFCC lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 30 publications
2
21
0
3
Order By: Relevance
“…In terms of radiologic factors, patients with the signal enhancement of carpal or distal ulna on MRI had higher pain NRS and DASH scores, and this was the only significant prognostic factor; almost none of the radiologic factors including degree of ulnar plus variance, type of TFCC lesion, or arthritis of ulno-carpal or distal radio-ulnar joint had a significant effect on the treatment failure for idiopathic UIS. These results are consistent with previous findings that diagnostic MRI findings and values are limited in TFCC injury 20 , suggesting that the diagnosis of UIS is made on clinical ground and supported by radiographic studies. However, MRI findings are often a precursor to plain radiographic findings 22 and our results suggest that carpal or distal ulna bone enhancement is distinctive and helps to predict the prognosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of radiologic factors, patients with the signal enhancement of carpal or distal ulna on MRI had higher pain NRS and DASH scores, and this was the only significant prognostic factor; almost none of the radiologic factors including degree of ulnar plus variance, type of TFCC lesion, or arthritis of ulno-carpal or distal radio-ulnar joint had a significant effect on the treatment failure for idiopathic UIS. These results are consistent with previous findings that diagnostic MRI findings and values are limited in TFCC injury 20 , suggesting that the diagnosis of UIS is made on clinical ground and supported by radiographic studies. However, MRI findings are often a precursor to plain radiographic findings 22 and our results suggest that carpal or distal ulna bone enhancement is distinctive and helps to predict the prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…The sex difference in treatment outcomes could in part be explained by higher physical vulnerability 16 or pain sensitivity 17 in women; musculoskeletal pain and disability were found to be more prevalent 18 and more severe in women 19 . The ulno-carpal stress test is reportedly highly sensitive but not specific for UIS; other ulno-capal pathology including lunotriquetral ligament injury or isolated ulno-carpal arthritis will produce positive findings 20 , 21 . However, our results suggests that pain NRS scores on ulno-carpal stress test in the presence of a history of ulnar wrist pain worsened by pronation or ulnar deviation of the wrist and plain radiograph with positive ulnar variance had significant prognostic value for conservative treatment of idiopathic UIS.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical tests were found to have low positive predictive values in the diagnosis of TFC lesions, ranging from 0.53 to 0.55. 12 Accordingly, in this study, TFC perforations were found in half of the patients with clinically diagnosed ulnar impaction syndrome. Diagnoses thereby, deliberately did not rely on MRIs because these demonstrated limited sensitivity and specificity as long as they were not done using a sophisticated technique under study conditions.…”
Section: Discussionmentioning
confidence: 53%
“…In addition to the data presented in table 3, the study of Schmauss et al presented the diagnostic accuracy of their tests separately for different subgroups. 25 These results are summarised in online supplemental appendix 2. Table 4 describes the accuracy of the diagnostic tests for non-chronic hand and finger injuries.…”
Section: Accuracy Of Diagnostic Tests Concerning Wrist Injuriesmentioning
confidence: 97%
“…Eight studies were retrospective [23][24][25][26][27][28][29][30] nine studies were prospective [31][32][33][34][35][36][37][38][39] and six studies [40][41][42][43][44][45] gave no description of the study design. Eight studies 23 25 27 31 33 36 43 45 included more than 60 participants; six of these studies 23 25 27 31 33 36 described wrist pathologies and two 43 45 described hand pathologies.…”
Section: Study Characteristicsmentioning
confidence: 99%